Magnetic Fabrics and Source Implications of Chisulryoung Ignimbrites, South Korea - Hong, Hoabin; Yu, Yongjae; Doh, Seong-Jae; Suk, Dongwoo; Kim, Jeongmin (Frontiers in Earth Science, 2016)
The anisotropy of magnetic susceptibility (AMS) of late Cretaceous ash-flow tuffs in Chisulryoung Volcanic Formation, southeastern Korea was studied to define the primary pyroclastic flow azimuth. AMS data revealed a dominant oblate fabric with a tight clustering of k3 (minimum axis of magnetic susceptibility) and shallow dispersal of k1 (maximum axis of magnetic susceptibility) and k2 (intermediate axis of magnetic susceptibility). Dominance of oblate fabrics indicates clast imbrications imposed by compaction and welding. Flow azimuth inferred from AMS data indicates the nearby intrusive welded tuff (IWT) as the source of calderas for ignimbrites. Such an inference is supported by geologic investigations, in which the IWT displays eutaxitic textures nearly parallel to its subvertical contacts. The results are compatible with a unique prolate fabric and an anomalously high inclination observed for the IWT, possibly produced by rheomorphic flows as the welded tuff is squeezed along the rough-surfaced dyke walls due to agglutination.